2017
DOI: 10.1038/srep42276
|View full text |Cite
|
Sign up to set email alerts
|

Beam wander relieved orbital angular momentum communication in turbulent atmosphere using Bessel beams

Abstract: Optical beam wander is one of the most important issues for free-space optical (FSO) communication. We theoretically derive a beam wander model for Bessel beams propagating in turbulent atmosphere. The calculated beam wander of high order Bessel beams with different turbulence strengths are consistent with experimental measurements. Both theoretical and experimental results reveal that high order Bessel beams are less influenced by the turbulent atmosphere. We also demonstrate the Bessel beams based orbital an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…In free-space a common problem is phase distortions, such as turbulence. Here BG modes do not show complete reconstruction [60], nor does the hybrid combination add value [61], but classical studies have suggested that perhaps such modes may be resilient to beam wander due to turbulence [62]. This is yet to be tested in the quantum regime.…”
Section: Discussionmentioning
confidence: 92%
“…In free-space a common problem is phase distortions, such as turbulence. Here BG modes do not show complete reconstruction [60], nor does the hybrid combination add value [61], but classical studies have suggested that perhaps such modes may be resilient to beam wander due to turbulence [62]. This is yet to be tested in the quantum regime.…”
Section: Discussionmentioning
confidence: 92%
“…hypergeometric-Gaussian, Bessel-Gauss, and Hankel-Bessel beams) instead of LG beams were able to mitigate the effects of disturbances owing to their self-healing and partial coherence features [19][20][21][22][23] . The bit error rates of the transmitted signals carried by high order Bessel beams show smaller values and fluctuations 24 . Apart from the bit error rates, other statistical properties, such as the variance of the fluctuations of the OAM, M 2 -factor, and the displacement error are less affected by these non-diffraction beams.…”
Section: Introductionmentioning
confidence: 99%
“…All these beams are based on solutions of Helmholtz wave equation in different coordinates systems, respectively. Due to its intrinsic nature, the non-diffraction beams have many applications e.g., micro particles manipulating, optical tweezer [6,7], nonlinear optics [8,9], and communications [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%